Variations in the crustal structure and strength of plate coupling along the Ryukyu subduction zone - Doo, Wen-Bin; Lo, Chung-Liang; Huang, Yin-Sheng; Wu, Wen-Nan; Wang, Shiou-Ya (Geoscience letters, 2023)
The Ryukyu trench-arc-back arc system is part of the subduction margins of the Philippine Sea plate. Previous studies have indicated that several geophysical and geological characteristics reveal significant variations (including convergent rate, topography, subducting slab angle etc.) along this subduction system. In addition, the strength of plate coupling and the potential of large earthquake occurrence in the Ryukyu subduction zone have been major subjects of debate for decades. To gain new insights into the spatial variations in the crustal structure and strength of plate coupling along the Ryukyu subduction zone, in the present study, based on three P-wave seismic velocity profiles, we construct density models for 2-D gravity modeling. Then, we estimate the mantle lithosphere buoyancy (H m ) using these three density models to determine the strength of plate coupling between the subducting Philippine Sea plate and the overriding Eurasian plate, which could provide information for evaluating large earthquakes potential. 2-D gravity modeling results reveal that oceanic plateaus and/or submarine ridges with obviously less dense and thick oceanic crust are subducting in the northern and central parts of the Ryukyu Trench, which could increase the slab buoyancy in these regions. The H m results indicate that the strength of plate coupling is almost weak in the north and is relatively strong in the central Ryukyu subduction zone.